Evolução da vulnerabilidade externa da economia brasileira de 2001 a 2011 - Gdikian, Fernando (2014)
This work aims to analyze the evolution of the external vulnerability of the Brazilian economy in the range 2001 to 2011, specifically from the perspective of monetary-financial sphere. The hypothesis is that external vulnerability tends to intensify in the long run when the current account deficits are financed with foreign capital and could become a barrier to economic development. Was observed with the data analysis of the balance of payments and international investment position of an improvement in the situation above external vulnerability by accumulating reserves. However, with the acceleration of economic growth in the mid-2000s, the structural external vulnerability manifested by deteriorating current account and the increase in net foreign liabilities